Daya hambat ekstrak buah mengkudu terhadap pertumbuhan Candida albicans - Muhammad Ilyas (DiscoverSys Inc., 2008)
Mengkudu contains saponin, flavanoid, atsiri oil and alkaloid that stated as antibacterialand antifungal. This study was a laboratory experimental with time series design thatused rejuvenatal Candida albicans as subjects and was held in Microbiology Laboratoryof Medical Faculty of UNHAS. This study was to find out the minimal inhibitingconcentration and force of mengkudu based on growth concentration of Candidaalbicans. SPSS program version 11.5 with Kruskal-Wallis test and Mann Witney test areused for data analysis. The result was Candida albicans had minimal inhibitingconcentration at 12% and the maximal at 16%.